Opportunities for Systematically Valuing Ecosystem Service Benefits Produced by Federal Conservation Programs. (April 2020) - Holmes, Thomas P.
Abstract : Federal agencies invest taxpayer dollars every year in conservation programs that are focused on improving a suite of ecosystem services produced on private lands. A better understanding of the public benefits generated by federal conservation programs could help improve governmental efficiency and economic welfare by providing science-based evidence for use in policy decision-making regarding targeting of federal conservation investments. Of specific concern here are conservation investments made by the U.S. Department of Agriculture (USDA). While previous research has shown that efficiency gains are possible using cost-benefit analysis for targeting conservation investments, agency-wide implementation of this approach by policy makers has been constrained by the limited availability of location-specific information regarding conservation benefits. Cost-effective opportunities for integrating location-specific ecosystem service valuation research with USDA conservation decision-making include: (1) institutionalizing funding of comparable studies suitable for benefit transfer, (2) utilizing non-traditional data sources for research complementing benefit transfer, and (3) creating a state-of-the-art program for developing and communicating research in ecosystem service valuation exemplifying the highest standards of scientific conduct.